BUILDING A COLLABORATIVE ECOSYSTEM: THE ROLE OF HIGHER EDUCATION INSTITUTIONS, INDUSTRY, AND GOVERNMENT IN ENHANCING GRADUATES’ EMPLOYABILITY (INTERNATIONAL SEMINAR, 2025)
Improving the quality of human resources (HR) is a key factor in addressing global challenges and the Industrial Revolution 4.0, particularly concerning the employability of university graduates entering the workforce. However, the gap between graduates’ competencies and labor market demands remains a significant issue in Indonesia. This study aims to understand how collaboration among universities, industries, and government—within the framework of the Triple Helix model—can effectively enhance graduates’ employability. Using a descriptive qualitative approach through literature review, this research analyzes various sources, policies, and case studies related to the implementation of the Triple Helix collaboration and the Merdeka Belajar–Kampus Merdeka (MBKM) policy. The findings reveal that curriculum misalignment with industry needs, limited practical experience, and a lack of soft skills are the main factors contributing to the competency gap among graduates. Synergistic collaboration among the three sectors can strengthen the development of applied curricula, internship programs, and skills training that are responsive to labor market dynamics. Nevertheless, the implementation of such collaboration still faces regulatory barriers, inter-institutional coordination challenges, and insufficient incentives for industry participation. Government programs such as Kedaireka offer strategic opportunities to address these obstacles, but they require greater institutional capacity building and more intensive cross-sector coordination. This study recommends strengthening the integration of the Triple Helix model as an innovative and adaptive educational ecosystem to bridge the gap between higher education and the workforce in Indonesia.